Malignancy Rate of Bethesda Class III Thyroid Nodules Based on the Presence of Chronic Lymphocytic Thyroiditis in Surgical Patients - Cho, Yoon Young; Chung, Yun Jae; Kim, Hee Sung (Frontiers in Endocrinology, 2021)
Background: Hashimoto’s thyroiditis (HT), also known as chronic lymphocytic thyroiditis (CLT), may interfere with the accurate cytological diagnosis of thyroid nodules. Recently, HT has been considered a premalignant condition for thyroid cancer development. The diagnosis of atypia of undetermined significance/follicular lesions of undetermined significance (AUS/FLUS) thyroid nodules is challenging and evidence for the malignancy risk of (AUS/FLUS thyroid nodules coexisting with CLT is scarce. Therefore, we assessed the malignancy risk of AUS/FLUS thyroid nodules according to the presence of background CLT.. Methods: This study included 357 surgically resected thyroid nodules with AUS/FLUS cytology. Cases with concomitant malignant nodules were excluded. CLT was defined based on the pathologic report after thyroid surgery. Results: Among 357 tumors, 130 tumors (36%) were confirmed to have coexisting CLT, and 170 tumors (48%) were determined to be malignant after thyroidectomy. Malignancy rates were similar in both groups (48% in each) regardless of background CLT (62/130 with CLT vs. 108/227 without CLT). In the group with CLT, thyroiditis was more frequent in the final pathology (12% with CLT vs. 1% without CLT, P = 0.003). In multivariate analysis, positive BRAFV600E mutation, highly suspicious sonographic features (K-TIRADS 5), and smaller thyroid nodules were significant factors for thyroid malignancies. Conclusion: The malignancy rate of thyroid nodules with AUS/FLUS cytology was comparable irrespective of the presence of underlying CLT.